2021
DOI: 10.2147/jmdh.s330647
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Research Capacity and Culture of Health Professionals Working with Women, Children and Families at an Australian Public Hospital: A Cross Sectional Observational Study

Abstract: Background: There is limited evidence for use of the Research Capacity and Culture tool across multidisciplinary health professionals. We explored using the Research Capacity and Culture tool among multidisciplinary health professionals at an Australian secondary hospital. Methods: A cross-sectional observational study where online and paper-based surveys of the Research Capacity and Culture tool were disseminated between November 2020 and January 2021. Descriptive analyses of demographic variables and Likert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, only if they are equipped with the appropriate knowledge and skills, resources, authority, and sufficient support from senior management [ 34 ] can team-level middle managers effectively operationalize this support to facilitate AHP research engagement [ 35 ]. Of note, a recent Australian study surveying multiple healthcare disciplines suggests that inadequate research skill/ support at team-level may be a problem specific to allied health research [ 36 ]. National research support organisations may therefore need to target resources and efforts specifically towards supporting AHP team managers, ensuring they have access to relevant training, mentorship and support.…”
Section: Discussionmentioning
confidence: 99%
“…However, only if they are equipped with the appropriate knowledge and skills, resources, authority, and sufficient support from senior management [ 34 ] can team-level middle managers effectively operationalize this support to facilitate AHP research engagement [ 35 ]. Of note, a recent Australian study surveying multiple healthcare disciplines suggests that inadequate research skill/ support at team-level may be a problem specific to allied health research [ 36 ]. National research support organisations may therefore need to target resources and efforts specifically towards supporting AHP team managers, ensuring they have access to relevant training, mentorship and support.…”
Section: Discussionmentioning
confidence: 99%
“…In describing the scale values in this way, the authors of this study do not outline or cite the construct validation process that enables the RCC tool to be categorised as such. It has been previously identified that the RCC tool does not provide cut off values to enable a meaningful interpretation of the score beyond the original definitions of the scale (1 = no success/skill; 10 = highest possible success/skill) [ 6 ].…”
Section: Main Textmentioning
confidence: 99%
“…Healthcare organizations with a strong research culture have greater productivity, higher retention of doctors and less patient mortality. (1,2) Research literacy which is required for this culture to prevail is deficient in many healthcare professionals. However, as evidence-based practices are gaining momentum, more organizations are now getting their professionals involved in research training and evidence generation.…”
Section: Introductionmentioning
confidence: 99%
“…Frameworks have identified necessary components for these systems including supportive governance, enabling organizational structures, research literacy of leaders, dedicated staff research positions, infrastructure, partnerships with universities, research skills, motivation and faculty participation. (1,3) Developed countries have shown great progress in transforming their health systems by establishing methods for evidence-based practices. Developing countries such as Pakistan still lag behind despite the rising research needs, as there is a general trend for producing medical practitioners rather than medical researchers.…”
Section: Introductionmentioning
confidence: 99%